RISET PRAKTIK EKSPERIMENTAL LAS BUSUR DENGAN MATERIAL AS STAINLESS STEEL UNTUK PENCIPTAAN BENTUK KATAK POHON - Santoso, Miky Endro (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2021)
ABSTRACTThis research is applied research using experimental practical research method, which uses arc welding on stainless steel shaft material. In this research, the three-dimensional form that is wanted to be created is a tree frog form. The research objective was to determine the various materials and equipment used in welding with arc welding techniques; identify the stages of the implementation of creation from the preparation stage, the working stage, and the final stage, so that the work creation process runs smoothly. The experimental practical research method was chosen because this method involves researchers directly in the experiment of creating works using arc welding techniques, accompanied by documentation and recording. This research produces a 3-dimensional work in the form of a tree frog, made of stainless steel shaft material and a conclusion. The results of this research can be developed into further research or the diversity of works or craft and art products that use stainless steel shaft material (such as furniture, metal crafts, sculptures, and so on). In addition, the results of this research can also participate and contribute to the diversity of ideas, forms and materials in the development of craft and art products in the creative industry in Indonesia.  Keyword: arc welding, experimental practical research, three-dimensional form, tree frog   ABSTRAKPenelitian ini adalah penelitian terapan dengan menggunakan metode riset praktik eksperimental, yang menggunakan las busur (arc welding) pada material as stainless steel. Dalam riset ini, bentuk 3 dimensi yang ingin diciptakan adalah bentuk katak pohon. Tujuan penelitian adalah mengetahui berbagai material dan peralatan yang digunakan pada pengelasan dengan teknik las busur; mengidentifikasi tahap-tahap pelaksanaan penciptaan dari tahap persiapan, tahap pengerjaan, dan tahap akhir, agar proses penciptaan karya berjalan lancar. Metode penelitian praktik eksperimental dipilih karena metode ini melibatkan peneliti secara langsung dalam eksperimen penciptaan karya dengan teknik las busur, disertai dokumentasi dan pencatatan. Riset ini menghasilkan sebuah karya 3 dimensi berbentuk katak pohon, dari material as stainless steel dan sebuah simpulan. Hasil penelitian ini dapat dikembangkan ke penelitian lanjutan atau keberagaman karya atau produk kriya dan seni yang menggunakan material as stainless steel (seperti furnitur, kriya logam, patung, dan sebagainya). Selain itu, hasil riset ini juga dapat berpartisipasi dan memberikan sumbangan keragaman ide, bentuk, dan material pada perkembangan produk kriya dan seni dalam industri kreatif di Indonesia. Kata kunci: bentuk tiga dimensi, katak pohon, las busur, riset praktik eksperimental